IMPLEMENTASI PENDIDIKAN KARAKTER PENDIDIKAN LINGKUNGAN SEKOLAH DI ERA PANDEMI COVID-19 PADA SISWA SEKOLAH DASAR - Marwanti, Endah; Nugroho, Irfan Adi (Universitas Sarjanawiyata Tamansiswa, 2021)
Education in today's pandemic requires better attention and readiness from both teachers and students. This diverse readiness also requires continuous learning and finding out to form the character of good students. In the present, students need to be continuously educated and understood related to character education. The purpose of this study is to describe how to instill the character of caring for the environment in schools and find out how teachers use devices as learning media during the Covid-19 pandemic. The method used in this research is descriptive qualitative. The results of the implementation of caring for the environment can be applied by school equipment to students, to foster and shape the character of students who are aware of the importance of preserving the environment and the importance of maintaining natural balance. The achievement of the environmental literacy movement is supported by teachers, school staff, and students and is equipped with optimal facilities to support the successful implementation of the optimal environmental literacy movement. The use of devices in the learning process is maximized as a substitute for the teacher in understanding the material for students. This is related to assessment because using online teachers also provides tolerance related to collecting and assessing assignments. The teacher always checks and warns students who have not collected the results of today's learning every afternoon, so that there is an opportunity for students who want to improve or even haven't done it. The diversity of learning platforms used is expected that the enthusiasm of students in learning will continue to exist so that they are not psychologically depressed too